Electrochemical model of euglena sanguinea ehrenberg stimulated with multi-level electromagnetic fields - K. Packamwongsang; S. Noppanakeepong; N. Naranong; P. Phaewbang; P. Pleuksananon; and W. Packamwongsang (My University, 2017)
This research aimed at studying the property of Euglena Sanguinea Ehrenberg (E. sanguinea) before and after being stimulated by multi-level electromagnetic fields (MLEM). After the stimulation, it was found that physical properties were changed, i.e., cell membrane and components deformed. Main biochemical compositions were changed in accordance with new electrochemical equation which was estimated from FTIR bands. Moreover, the estimated electrical results before and after being stimulated, i.e., impedance and complex relative permittivity of main biochemical compositions from extraction, were then measured, simulated, and compared by means of Cole-Cole plot technique which yielded the statistic correlation 0.89 at 95% confidence level. Semi-circle impedance was related to complex relative permittivity as its value decreased with the increasing frequency. These were the information for designing the new electrical equivalent circuit model of E. sanguinea with MLEM to explain many phenomena in cell. The relationship between energy from MLEM system and bond energy of main biochemical compositions of E. sanguinea as well as between electromagnetic field behaviors of MLEM system which stimulated to cell and induced voltage transmitted through each biochemical compositions of E. sanguine were also identified.
Keywords: Microbial Inactivation Methods